Customer loyalty attributes, satisfaction and behavioural loyalty / Nurul Nadiah Azizan - Azizan, Nurul Nadiah (2013)
Customer loyalty is the relationship that the customer devotes with the provider and the customer will be regularly using the service of the provider. This paper studies the perspective of hotel’s customer in determining their loyalty as the loyalty behavior of customers will bring enormous profit and prosperity to the hotel’s organization. This study also focused on the role of satisfaction as a mediator of the relationship between customer loyalty attributes and behavioural loyalty. Multiple regression and Bootstrap analysis had been used to test a series of the hypotheses. The finding showed there were relationships between customer loyalty attributes, satisfaction and behavioural loyalty. However, the findings were not statistically significant for the attributes of customer loyalty. Finding showed perceived value and attachment had a relationship with satisfaction and behavioural loyalty. Conversely, familiarity did not encompass a relationship towards satisfaction and satisfaction also did not act as a mediator between customer’s familiarity and behavioural loyalty. Important implications for hoteliers and academicians been discussed through the investigation of this study.